Studi Kebutuhan E-learning untuk Kegiatan Pembelajaran di SMP se-Kecamatan Jebus - Syamsilahuddin Norman (Student Research Journal, 2023)
Online learning that is currently being implemented is forcing the world of education to implement internet-based learning media, one of which is e-learning. The purpose of this study was to obtain an overview of the need for e-learning for learning activities in junior high schools throughout Jebus District. The method used in this research is descriptive research with the subject of the research are junior high school teachers in Jebus District, totaling 38 respondents. Data collection was carried out using a questionnaire distributed through the Google Form platform. The results of the study indicate that there is a need for the development of e-learning that pays attention to several aspects in it, namely being integrated with video learning media, text, images, and other interactive media. It is recommended to conduct follow-up research related to the development of e-learning tools